2000
DOI: 10.1007/s001250051459
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing incidence of major amputations in people with diabetes

Abstract: In the St Vincent Declaration Action Programme 1992 [1] a number of 5-year targets were outlined, one being the intention to reduce by one-half the rate of lower limb amputation for diabetic gangrene. Considering the small amount of evidence at that time supporting this demand [2±7], it is surprising that a number of recent reports [8±16] to a large extent have fulfilled these requirements. The purpose of this paper is to document the incidence of major amputations in diabetic patients in a 15-year period in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
3
17

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(84 citation statements)
references
References 14 publications
3
61
3
17
Order By: Relevance
“…These data were also almost similar to previous local studies 43,44. Patients’ foot examination and advice regarding foot care from attending physicians will increase patients’ confidence in managing their foot-care practices 20,41…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These data were also almost similar to previous local studies 43,44. Patients’ foot examination and advice regarding foot care from attending physicians will increase patients’ confidence in managing their foot-care practices 20,41…”
Section: Discussionsupporting
confidence: 85%
“…A majority of diabetic foot complications can be prevented by patient foot-care practices on a regular basis 41,42. Contrary to this recommendation, in the present study, only 41.7% of diabetic patients’ self-examined their feet.…”
Section: Discussioncontrasting
confidence: 79%
“…In our current understanding, there are 3 main types of diabetes which have been confirmed: type 1 diabetes, type 2 diabetes and gestational diabetes. Diabetes is the primary reason for adult blindness, end-stage renal disease (ESRD), gangrene and amputations (2225). Being overweight, lack of exercise, family history and stress increase the likelihood of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, several studies have been published on the decreasing incidence of lower limb amputations (LLAs) in the diabetic population (Holstein et al 2000, Calle-Pascual et al 2001, van Houtum et al 2004, Ekelinen et al 2006, Trautner et al 2007, Larsson et al 2008, Canavan et al 2008). Although the rate of LLA due to peripheral vascular disease in the non-diabetic population has shown a similar trend (Holstein et al 2000, Calle-Pascual et al 2001, Ekelinen et al 2006), unchanged or even increased rates of non-diabetic LLA have been reported (Trautner et al 2007, Canavan et al 2008).…”
mentioning
confidence: 99%